Study of sound absorption by using acoustic impedance tube - Chan, Qi Si. (2012)
Acoustic absorption is the process of reducing sound energy by passing sound waves through a medium or striking a surface. The absorptivity is the property of a material that converts the acoustic energy of sound waves into another form of energy, usually heat, so as to control noise within a boundary. The absorptivity of a given material depends on frequency and is affected by size, shape, location, and the mounting method used.